1982
DOI: 10.1159/000250123
|View full text |Cite
|
Sign up to set email alerts
|

Does Mast Cell Protection plus Mediator Antagonism Surpass the Effect of a Classic Antihistaminic in the Treatment of Chronic Urticaria?

Abstract: A new type of antiallergic drug, oxatomide (60 mg daily), was compared with the antihistaminic, mequitazine (10 mg daily), in a 5-week double-blind randomized study involving 26 patients with chronic urticaria. In the 13 oxatomide-treated patients, papules, erythema and pruritus were significantly suppressed after 2 weeks, which was markedly more rapid than with mequitazine. Slight somnolence was reported by 3 patients on oxatomide and 1 on mequitazine; in the latter case, severe urine retention was also repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
(11 reference statements)
0
5
1
Order By: Relevance
“…This investigation could not confirm the previously reported benefits of oxatomide [3][4][5]7] compared to other antihistaminic drugs. It is our opinion that the drug may be used in chronic urticaria in the same manner as other antihistamines.…”
Section: Resultscontrasting
confidence: 90%
“…This investigation could not confirm the previously reported benefits of oxatomide [3][4][5]7] compared to other antihistaminic drugs. It is our opinion that the drug may be used in chronic urticaria in the same manner as other antihistamines.…”
Section: Resultscontrasting
confidence: 90%
“…With regard to terfenadine, our results are in agreement with those of Kulshresta et al (1978) who administered the drug in exactly the same doses as ours to 12 volunteers and also found no anticholinergic effect. As for mequitazine, it must be noted that undesired anticholinergic effects (dry mouth, visual disorders, retention of urine) have been reported with this drug in patients on long-term treatment (Dry et al, 1980;Demaubeuge et al, 1982;Richards et al, 1984;Beaumont c al., 1986). The lack of anticholinergic activity of mequitazine in our study might be due to the small number of subjects and/or the short duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study in healthy volunteers desired pharmacological properties, possess was to evaluate comparatively the anticholinergic undesired anticholinergic activity is limited on effects of atropine and of two antihistamines: account of their side-effects (dry mouth, visual one, mequitazine, with anticholinergic activity disorders, constipation, retention of urine), inter- (Dry et al, 1980;Demaubeuge et al, 1982; actions with other drugs and contra-indications Richards et al, 1984;Beaumont et al, 1986), (e.g. prostatism, glaucoma) (Bowman & Rand, the other, terfenadine, without this activity 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The condition may put quite a strain on the individual affected, since itching may be very severe. This itching usually interferes 1 General Practitioner, Rue de la Chapelle 7 1, B-7370 Dour (Elouges). Belgium.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, there is still room for effec tive antipruritics. Oxatomide is a new, orally active antiallergic agent which not only competes with histamine, serotonin and SRS-A at the receptor level, but which also inhibits the release of mediators by the mast cell [4], Dermatological studies have shown oxatomide to be superior to a placebo in re lieving itching associated with urticaria [2,8] and atopic dermatitis [6], Oxatomide also compares favourably with the Hi-antagonist mequitazine in the treatment of urticarial pruritus [1], In view of these findings, a con trolled study of oxatomide in pruritus senilis was designed. The trial was performed in the winter when the condition is worse and any improvement is unlikely to be due to season al factors.…”
Section: Introductionmentioning
confidence: 99%